Die predikantsamp. Deel 2: Op soek na ’n Bybelse visie van die amp: Ironieë en verrassings. - Burger, CW; Wepener, CJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
The office of the minister. Part 2: In search of a Biblical vision for the office: Ironies and surprises. In this second article in our series on the office of the minister, the Bible will be looked at as a source for clarity on the essence of this office. People are often disappointed when they cannot find clear answers on questions concerning for example the office of the minister in the Bible, or that the answers that they find are not the answers they were actually looking for. The Bible however is often clear on other aspects regarding the office of the minister. Without giving the pretence of a complete Biblical inquiry on the office of the minister, six aspects on which the Bible is clear are presented and discussed after a very preliminary survey of the Old- and New Testament in this regard. Thereafter the six aspects is presented. These aspects will later, along with the findings from articles 1, 3 and 4 in this series, be used in order to formulate a systematic model for the understanding of the office of the minister in the fifth article.